The impact of consumer protection in the digital age: Evidence from the European Union - Anja Rösner; Justus Haucap; Ulrich Heimeshoff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We investigate the effect of an EU-wide consumer protection regulation on consumer trust as well as consumer behavior. The Unfair Commercial Practice Directive (UCPD) was implemented by EU member states between 2007 and 2010. We utilize data from the Special and Flash Eurobarometer for the years between 2006 and 2014 and experts' evaluation on consumer protection levels before the introduction of the regulation. This rich data set allows us to apply a difference-in-difference estimator with multiple time periods. We find a significant relationship between the introduction of the UCPD and consumer trust and cross-border purchases for countries with a low consumer protection level before the introduction of the UCPD. The relationship increases over time and stays then relatively constant.
Keywords: D18; K20; L50; L51; 330; Consumer Protection; UCPD; B2C; E-Commerce; Consumer Trust; Cross-border Purchase